Creep‐Induced Microstructure Evolution of Type 2205 Duplex Stainless Steel during Continuous Annealing Processing. Issue 5 (25th January 2014) - Park, Heeyong; De Cooman, Bruno C.
<x xml:space="preserve">Abstract</x> Superplastic behavior at 1323 K (1050°C) results in the pronounced creep deformation of cold rolled type 2205 duplex stainless steel during continuous annealing process. This superplastic behavior was evaluated by strain rate sensitivity measurements carried out in the 1273–1373 K (1000–1100°C) temperature range. The superplastic behavior was associated with the grain boundary diffusion in the steady state creep stage. Continuous dynamic recrystallization of ferrite was observed during the creep deformation and static recrystallization of austenite was observed in the early stage of the creep deformation. The 3D phase morphology was investigated in specimens annealed with and without applied stress. The stress applied during continuous annealing had a clear influence on the phase morphology which changed from an elongated and flat "pancaked" microstructure into a microstructure with island‐like austenite embedded in a ferrite matrix.